Prenatally diagnosed case of 22q11.2 deletion syndrome associated with pulmonary artery aneurysm - Ozer, Leyla; Lembet, Arda; Uğurlu, Nil; Baltaci, Volkan; Balci, Sevim (The Turkish Journal of Pediatrics, 2012)
Here, we report a new case with chromosome 22q11 deletion and cardiac anomaly diagnosed prenatally by echocardiography. Fluorescence in situ hybridization (FISH) analysis demonstrated a heterozygous deletion at 22q11.2. Echocardiography revealed ventricular septal defect, pulmonary atresia, and aneurysm of the main pulmonary artery and its branches. Pulmonary artery aneurysm (PAA) is rarely seen in patients with 22q11.2 deletion syndrome (22qDS). In this case, PAA was found by prenatal echocardiographic examination at the 25th week of gestation. To date, no prenatally diagnosed case of 22qDS with PAA has been reported. This is the first 22qDS case with PAA that was detected prenatally by FISH analysis.